2020
DOI: 10.1111/hdi.12876
|View full text |Cite
|
Sign up to set email alerts
|

Coronavirus disease 2019 (COVID‐19) in two pediatric patients with kidney disease on chronic immunosuppression: A case series

Abstract: Coronavirus disease 2019 (COVID‐19) is a highly infectious disease caused by the severe acute respiratory syndrome coronavirus 2 virus (SARS‐CoV‐2). While children appear to experience less severe disease than adults, those with underlying conditions such as kidney disease may be more susceptible to infection. Limited data are present for children with kidney disease, and there are limited prior reports of pediatric hemodialysis patients with COVID‐19. This report describes the mild clinical disease course of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 16 publications
0
11
0
Order By: Relevance
“…Two studies reported that HD patients tested positive for SARS-CoV-2 RNA on repeated testing despite being negative on two prior consecutive nasopharyngeal swabs [ 138 , 140 ]. Prolonged viral RNA shedding has been reported until 79 days in an adult HD patient [ 140 ] and 28 days in a pediatric patient [ 141 ]. Only one anecdotal case of reinfection has been reported in a dialysis patient [ 142 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Two studies reported that HD patients tested positive for SARS-CoV-2 RNA on repeated testing despite being negative on two prior consecutive nasopharyngeal swabs [ 138 , 140 ]. Prolonged viral RNA shedding has been reported until 79 days in an adult HD patient [ 140 ] and 28 days in a pediatric patient [ 141 ]. Only one anecdotal case of reinfection has been reported in a dialysis patient [ 142 ].…”
Section: Resultsmentioning
confidence: 99%
“…In research articles reporting clinical manifestation and outcome of COVID-19 patients (78 [54.4%]) the diagnosis of SARS-CoV-2 infection relied principally on RT-PCR (52 [63.4%]) [11-20, 32, 61, 62, 69, 93, 94, 100, 108-111, 113, 115-124, 126, 129, 132, 134, 135, 138-151], serology (4[6.3%]) [18, 20, 22-24, 86, 99], RT-PCR and serological assay (5[6.6%]) [29-31, 85, 127, 152] or a combination of diagnostic tests including clinical evaluation [6,13,19,21,112,114,125,128,130,131,133,136,137,153,154]. Fever, fatigue, poor appetite, headache and lymphopenia at lab tests Chest X-ray negative for COVID-19 lesions Case-report [141] Fever, body aches, cough, fatigue and nasal congestion Case-series (one out of three patients was symptomatic) [149] Outcomes of the confirmed COVID-19 HD patients Outcome of patients on in-centre HD was evaluated on 52 (35.9%) articles including 12,365 patients (range 11-3160) COVID-19 patients (Table 3S). Studies come principally from China (15.3%), Italy (15.3%) and Spain (11.5%); 3.8% of the studies included European authorship.…”
Section: Diagnosismentioning
confidence: 99%
“…In-center HD patients may represent a high-risk group because of a lack of private transportation and isolated rooms, and being in close contact with other patients and HD staff [20,31]. Private transportation was accessible in 49% of the centers in our study.…”
Section: Discussionmentioning
confidence: 76%
“…Contrary to adult experience [18], based on limited data, PN patients, i.e., hemodialysis (HD) and kidney transplantation patients, and those on immunosuppressive treatment were reported to have a lower risk. In addition, these children did not have an increased risk compared to healthy pediatric populations [19,20].…”
Section: Introductionmentioning
confidence: 99%
“…A global study reported no case of severe illness or MIS-C in 113 children with kidney disease in immunosuppressive therapy [5]. Also, a Spanish retrospective study of 26 patients [8] and two case reports [9] described a mild clinical course of infection in children with kidney disease, with no case of PICU admission.…”
Section: Discussionmentioning
confidence: 99%